Modified Newtonian Dynamics (MOND) vs Newtonian Dynamics: The Simple Test to Solve the Constant Speed of Galaxy Rotation - Huda Nasrulloh (JPSE (Journal of Physical Science and Engineering), 2022)
The rotation curve of galaxies for M33 in 1959 by Louise Volders gave the new hypothetical about the invisible matter that contributes inside of the galaxy, which later we call dark matter (DM). However, recently the theory about DM is still incomplete to understand this matter. This situation makes some scientists look for alternative ways such as f(R) gravity and conformal gravity theory. We have studied Modified Newtonian Dynamics (MOND) and Newtonian Dynamics (ND). We try to show the simple model that aims to give an analysis that MOND can correct to solve the constant speed of galaxy rotation. For simplicity, we consider the value of α = 1. The graph shows that the MOND model has a constant speed of 100 kilometres per second. While for the ND model, the speed will decrease for radius goes to infinity because the speed is dependent on r. Based on this result, we obtain that MOND can show the constant speed of galaxy rotation than ND. This result can conclude that MOND can solve the rotation curve of the galaxy.DOI: 10.17977/um024v7i12022p001